Priorities for transgender medical and healthcare research. Issue 2 (April 2016) - Feldman, Jamie; Brown, George R.; Deutsch, Madeline B.; Hembree, Wylie; Meyer, Walter; Meyer-Bahlburg, Heino F.L.; Tangpricha, Vin; T'Sjoen, Guy; Safer, Joshua D.
Abstract : Purpose of review: Transgender individuals experience unique health disparities but are the subject of little focused health research. This manuscript reviews current literature on transgender medical and mental health outcomes and proposes research priorities to address knowledge gaps. Recent findings: Published research in transgender healthcare consists primarily of case reports, retrospective and cross-sectional studies, involving largely European settings. Challenges to US-based transgender health research include a diverse population where no single center has sufficient patient base to conduct clinical research with statistical rigor. Treatment regimens are heterogeneous and warrant study for best practices. Current research suggests increased mortality and depression in transgender individuals not receiving optimal care, and possibly a modest increase in cardiovascular risk related to hormone therapy. Current evidence does not support concerns for hormone-related malignancy risk. Summary: The priorities for transgender medical outcomes research should be to determine health disparities and comorbid health conditions over the life span, along with the effects of mental health, medical, and surgical interventions on morbidity and mortality. Specific outcomes of interest based on frequency in the literature, potential severity of outcome, and patient-centered interest, include affective disorders, cardiovascular disease, malignancies, fertility, and time dose-related responses of specific interventions.